Avaliação do conhecimento e do cuidado relacionados à saúde ginecológica da atleta brasileira participante dos Jogos Olímpicos do Rio de Janeiro – 2016 - Parmigiano, Tathiana Rebizzi [UNIFESP] (2020)
Objective: To investigate knowledge and care related to gynecological health of the Brazilian female athletes participating of the 2016 Summer Olympic Games held in Rio de Janeiro, Brazil. Material and Methods: An observational study was elaborated and proposed through an online questionnaire drawn up by Informatics Health Department of the Sao Paulo Federal University. It was based on Google Forms and was sent by email to the participants. This tool is an adapted online version of a validated questionnaire for specific evaluation of female athletes – Pre- participation Gynecological Evaluation of Female Athletes (PPGE). The inclusion criterions were: to be female, older than 16 years old and be a participant of the event. This study was approved by Research Ethics Committee of Sao Paulo Federal University under the registration 0761/2016, CAAE 1.615.280. Results: The athletes practiced 28 different sportive modalities, mean age of 27±5 years old. For 66% of them, it was the first Olympic participation. Most of them had already menstruated (99%). They referred the use of contraceptive methods, mainly oral ones (61%). 77% believed that vaginal bleeding influences sportive performance and 63% preferred to compete after it. Only 26% would not compete in their phase of choice. Anxiety symptoms, bloating, increased appetite, depression and dysmenorrhea were referred by 52% of them. Among these, 49% related that these symptoms worsen the sportive performance. The percentual of athletes who had no knowledge about Female Athlete Triad was 56%. 77% referred weight concern and the majority were on a diet. The use of diuretics, laxative or vomiting for weight loss was related at some point by 11% of them, being more prevalent among those who were on a diet. Among these, 77% referred to use these methods to optimize the loss. In relation to urinary incontinence, 67,5% of them knew about Athletic Urinary Incontinence and 40% referred urinary loss at same point. 31% also referred drop in performance. Mostly the participants had access to multidisciplinary follow up, psychological (83%), nutritional (96%) and gynecological (83%) during the Olympic cycle. Conclusion: Most of Brazilian Olympic athletes use hormonal contraceptives, mainly orally. They present physical and mood symptoms related to vaginal bleeding and try to plan their flow to optimize the sports performance. Besides the multidisciplinary follow up, they, still, do not know the affections to which they are exposed as the Female Athlete Triad, present athletic urinary incontinence and put their health at risk to weight control.